Identification of Phytochemical Extract of a Combination of Young Coconut Water, Ginger and Turmeric - Hasti, Florentina Saji; Kopon, Aloisius Masan; Baunsele, Anselmus Boy; Tukan, Maria Benedikta; Leba, Maria Aloisia Uron; Boelan, Erly Grizca; Komisia, Faderina (Indonesian Journal of Chemical Research, 2022)
Turmeric is a tropical plant that is widely found on the Asian continent which is extensively used as a food coloring agent and fragrance. Ginger is a spice plant that it often found in South Asia which is widely has spread throughout the world. Coconut is an annual plant, has a hard stem and is generally not branched (monopodial), has fibrous roots, and contain water that is clear and tastes sweet, young coconut water has benefits such as antibacterial, beauty treatment, as an isotonic agent, and carry out the urination. This research was conducted to obtain information about the physicochemical properties and secondary metabolites contents of the coconut water, ginger and turmeric combination extract. The research method was carried out by mixing the mashed turmeric and ginger with the young coconut water and then macerated. The resulting extract was then tested for physicochemical properties (solubility) and identified groups of secondary metabolites (flavonoids, tannins, saponins, and steroids/triterpenoids. The extract was soluble in 70% ethanol. In addition, the combination of young coconut water, ginger, and turmeric extract contain a group of secondary metabolites among others flavonoids, tannins, saponins, and triterpenoids.